Executive cognitive function and cessation of smoking among older smokers - Tait, Robert; Siru, R. (2009)
The prevalence of smoking among the elderly is lower than in the general population, but aging populations in many countries mean that smoking-related diseases will increase as a health burden in the future. Executive cognitive functioning (ECF) allows people to plan and regulate behavior in order to achieve future goals. Impaired EGF is prevalent in those aged over 65 years and may be a factor in continued smoking among the elderly. Initial studies suggest that current ECF predicts successful cessation of smoking. Among ever smokers, 74% of those with unimpaired ECF had successfully quit compared with 65% of those with some level of ECF impairment. However, a general measure of cognition did not predict cessation. These findings have implications for how cessation of smoking programs can be improved in order to help older smokers quit smoking by providing more social support as well as the removal of smoking cues. © 2009 Future Medicine Ltd.